1991
DOI: 10.1103/physrevlett.67.1844
|View full text |Cite
|
Sign up to set email alerts
|

Photon-stimulated charge transfer in condensedO2studied by negative-ion desorption

Abstract: Photon-stimulated desorption of negatively charged ions from condensed O2 is observed in the 17-42-eV photon energy range. Two classes of photon-stimulated charge-transfer processes, i.e., resonant processes via the formation of highly excited states of the condensed molecules and nonresonant processes involving energetic photoelectrons, are considered to account for these observations. PACS numbers: 31.70. Ks, 33.80.Eh, 68.45.Da, 79.20.Ds The charge-transfer process is of fundamental importance to many are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1992
1992
2006
2006

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…The VUV photochemistry of O 2 adsorbed on a polycrystalline Pt [166] or Si surface [13] was investigated by Dujardin et al Both O + and O − were observed to desorb from multilayers of O 2 physisorbed on Pt for irradiation with 17 eV photons, with a strong increase above 32 eV. O + 2 and O − 2 were also observed but with much lower probabilities.…”
Section: Omentioning
confidence: 99%
“…The VUV photochemistry of O 2 adsorbed on a polycrystalline Pt [166] or Si surface [13] was investigated by Dujardin et al Both O + and O − were observed to desorb from multilayers of O 2 physisorbed on Pt for irradiation with 17 eV photons, with a strong increase above 32 eV. O + 2 and O − 2 were also observed but with much lower probabilities.…”
Section: Omentioning
confidence: 99%
“…However, relatively little work has been undertaken to study photon-stimulated desorption of negative ions. [1][2][3][4][5] Several photodissociation/photodesorption mechanisms have been proposed. [6][7][8][9][10][11][12][13] For the desorption of negative ions, the incident photon may excite the adsorbed molecule AB to a neutral Rydberg state.…”
Section: Introductionmentioning
confidence: 99%